Modifikasi Algoritma Semut untuk Optimasi Probabilitas Pemilihan Node dalam Penentuan Jalur Terpendek - Erlin Windia Ambarsari (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
LPPM Unindra's Dipa Research Grantprogress report on the searching of the shortest route previously made by the researcher with the title Analysis of the Effectiveness of the Shortest Route Using Ant Algorithm Method and LeadTime Approach: Case Study of Toko Gamis Murah Jakarta in 2014 showsan imperfect route selection, especially the one which is randomly conducted, leading to the chance of output route to be selected is once in a cycle. This causes the iteration conductedtosearch the shortest route will take a longer time. The purpose of this study is to modify the algorithm for finding the shortest route by inserting the Fuzzy C-Means Algorithm into node selection probability of the ant algorithm to allow the route chosen during the cycle to continuouslyperform that iteration conducted in the shortest route searching calculation is not too long because the route value convergence is more quickly obtained. This research collects qualitative data from goods delivery route to Toko Gamis Murah Jakarta's customers, with the result showing CGFEDBA route (32.5 km) with 100% probability, DFEGCBA (34.6 km) with 93. 75% probability and FGEDCBA (37.5 km) with 93.75% probability.